2005
DOI: 10.1038/sj.onc.1208641
|View full text |Cite
|
Sign up to set email alerts
|

KIF14 is a candidate oncogene in the 1q minimal region of genomic gain in multiple cancers

Abstract: Gain of chromosome 1q31-1q32 is seen in >50% of retinoblastoma and is common in other tumors. To define the minimal 1q region of gain, we determined genomic copy number by quantitative multiplex PCR of 14 sequence tagged sites (STSs) spanning 1q25.3-1q41. The most frequently gained STS at 1q32.1 (71%; 39 of 55 retinoblastoma) defined a 3.06 Mbp minimal region of gain between flanking markers, containing 14 genes. Of these, only KIF14, a putative chromokinesin, was overexpressed in various cancers by real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
175
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(183 citation statements)
references
References 39 publications
7
175
1
Order By: Relevance
“…It was interesting to see that, to the exception of PLU-1/JARID1B (Lu et al, 1999), all the genes identified in our study were newly proposed as candidate cancer genes. Furthermore, MUC1 (Schroeder et al, 2004), a long known cell surface marker overexpressed in a sizeable fraction of breast tumours, and KIF14 (Corson et al, 2005), a recently proposed candidate at 1q31, presented DSs below the threshold and were excluded from our selection. Genes selected in our study belong to rather diverse functional groups, of which three appeared prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…It was interesting to see that, to the exception of PLU-1/JARID1B (Lu et al, 1999), all the genes identified in our study were newly proposed as candidate cancer genes. Furthermore, MUC1 (Schroeder et al, 2004), a long known cell surface marker overexpressed in a sizeable fraction of breast tumours, and KIF14 (Corson et al, 2005), a recently proposed candidate at 1q31, presented DSs below the threshold and were excluded from our selection. Genes selected in our study belong to rather diverse functional groups, of which three appeared prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…2 Reverse transcription (RT)-PCR expression analyses of all genes in this region showed that only KIF14 (kinesin family member 14), a poorly characterized kinesin, was overexpressed 31-to 92-fold in 4 breast cancer cell lines compared with healthy breast tissue. Robust, cell line-specific protein expression, paralleling the mRNA level, was confirmed by immunoblot.…”
mentioning
confidence: 99%
“…Among the lung tumors, KIF14 mRNA overexpression showed a strong trend toward association with decreased survival. 2 Although cloned several years ago, 3 KIF14's cellular function is not yet clear. A recent report indicates that KIF14 inhibition causes a delay in the metaphase-to-anaphase transition, characterized by misaligned chromosomes that oscillate abnormally between the spindle pole body and the metaphase plate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 KIF14 is a microtubule motor that is amplified and overexpressed in breast cancer, lung cancer, and retinoblastoma. 15,47 It has been demonstrated that altered KIF14 mRNA expression is a prognostic indicator for patients with breast cancer and lung cancer. 15,17 The absence of KIF14 in HeLa cells reportedly resulted in a failure to complete cytokinesis, producing binucleated cells that underwent apoptosis after failed mitosis.…”
Section: Kinesin-2 Familymentioning
confidence: 99%